Energy absorption of foam-filled multi-cell composite panels under quasi-static compression. (15th November 2018) - Chen, Jiye; Fang, Hai; Liu, Weiqing; Zhu, Lu; Zhuang, Yong; Wang, Jian; Han, Juan
Abstract: This paper reports on the energy absorption characteristics of four types of innovative foam-filled multi-cell composite panels (FMCPs) composed of glass fiber reinforced polymer (GFRP) face sheets, GFRP lattice webs, and polyurethane (PU) foam. Quasi-static compression experiments on the FMCPs manufactured by a vacuum assisted resin infusion process (VARIP) were performed to demonstrate the feasibility of the proposed panels. Compared with the traditional FMCP with double-layer orthogonal foam cells, a maximum decrease in the peak crushing force (PCF) of approximately 148% was obtained for the FMCP with trapezoidal cells. Moreover, the enormous decrease in bearing load has been overcome by the proposed FMCPs. Among the four proposed FMCPs, the FMCP with double-layer dislocation cells exhibited the greatest specific energy absorption (SEA) capacity and the highest mean crushing load (MCL). Several numerical simulations using ANSYS/LS-DYNA were conducted on the FMCP with double-layer dislocation cells to parametrically investigate the effects of the face-sheet and lattice-web thickness, the foam-cell height, the foam-cell width, and the foam density. The effectiveness and feasibility of the numerical model were verified by the experimental results. The numerical results demonstrated that thicker face sheets and lattice webs, higher foam densities, and narrower foam cells can significantly increase the PCF and bearing load decrease. Moreover, the PCF and bearing load decrease were hardly affected by the foam-cell height.